An Evaluation of the Necessity and Significance of Human Values in Higher Education - Sinha, Suhrid; Sinha, Juli; Sinha, Saurav (International Journal of Psychosocial Rehabilitation, 2019)
We live in a world that is contracting, where the old culture of competitiveness and conflict must make way for a new culture of convergence and cooperation. The search for serenity and happiness is going through an unparalleled crisis on a global scale right now. A man is perplexed about where he can find love, motivation, and trust. Selfishness has turned into the guiding principle of human endeavor. We have forgotten what makes us all part of the same human family in the first place. It is clear from the increase in instances of violence, rape, exploitation, and fraud. Incorporating a spiritual component into our new educational philosophy has become a need. The University Grant Commission is supporting human values education in universities and colleges as part of the Tenth Plan. A person upholding human values of truthfulness, righteousness, peace, love, and nonviolence is said to be a true human being. The fundamental problem of rebuilding a society with proper values must be addressed in the face of persistent pressure from materialism, wrapped in the language of development.